Patient Satisfaction with the Service Quality Dimensions In Multi-Speciality Private Hospitals in Indore City MP, India - Katira, Shilpa; Samuel, Rajeev; Tiwari, Shefali; Pai, Deepali; Agrawal, Surya (SAN Scientific, 2024)
The healthcare industry in India is evolving rapidly, with intense competition among private sector hospitals where consumers demand higher quality services. This study investigates the relationship between service quality factors and patient satisfaction in the competitive private healthcare sector, focusing on private hospitals in Indore City. It offers insights into how service quality dimensions-reliability, responsiveness, and empathy-impact patient perceptions and satisfaction. To succeed, private hospitals must enhance both medical and functional service quality to meet patients' elevated expectations. The study surveyed 300 patients from CHL Hospital, Bombay Hospital, and Medanta Hospital in Indore. Using the Parasuraman Scale, a self-administered questionnaire with 26 items (22 on service quality perception and 4 on patient satisfaction) was developed and rated on a 5-point Likert scale. Data analysis involved correlation and regression tools to assess the impact of each service quality factor on patient satisfaction. The researcher personally visited the facilities and, with permission from the Personnel Officer, collected data directly from patients regarding their satisfaction levels. This research provides critical insights for private hospitals striving to enhance service quality and remain competitive in a dynamic healthcare environment.